2018
DOI: 10.21873/invivo.11161
|View full text |Cite
|
Sign up to set email alerts
|

Expand+In Vivoiv.iiarjournals.orgIn Vivo September-October 2017 vol. 31 no. 5 1003-1009 Elevated Serum AA/EPA Ratio as a Predictor of Skeletal Muscle Depletion in Cachexic Patients with Advanced Gastro-intestinal Cancers

Abstract: ΔPMI (CC=0.443, p=0.039). In contrast, serum CRP, AA/EPA ratio and n-6/n-3 ratio were negatively related to ΔPMI p=0.006, p=0.018, p=0.025, respectively). On multiple regression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…43 Furthermore, Kitagawa et al reported that the n-6/n-3 ratio and arachidonic acid (AA)/ EPA ratio were associated with skeletal muscle depletion in cachexic patients with advanced gastrointestinal cancers. 44 In our study, we also found a negative correlation between the n-6/n-3 ratio and AA/EPA ratio and skeletal muscle mass. The effect of n-3 PUFA supplementation on sarcopenia is controversial, but randomized controlled trials have been conducted to elucidate the impacts of n-3 PUFAs on sarcopenia in older individuals.…”
Section: Discussionsupporting
confidence: 76%
“…43 Furthermore, Kitagawa et al reported that the n-6/n-3 ratio and arachidonic acid (AA)/ EPA ratio were associated with skeletal muscle depletion in cachexic patients with advanced gastrointestinal cancers. 44 In our study, we also found a negative correlation between the n-6/n-3 ratio and AA/EPA ratio and skeletal muscle mass. The effect of n-3 PUFA supplementation on sarcopenia is controversial, but randomized controlled trials have been conducted to elucidate the impacts of n-3 PUFAs on sarcopenia in older individuals.…”
Section: Discussionsupporting
confidence: 76%
“…This result reflects also to similar findings of a study conducted by Wilson D. Lo et al, where the psoas density was the predictor of outcome after enterocutaneous fistula repair [ 40 ]. However in our study the PMI and CRP values were negatively correlated but were statistically non-significant, any decrease of PMI could be considered to be associated with CRP elevation, the important marker of inflammation [ 41 ].…”
Section: Discussionmentioning
confidence: 89%
“…EPA appears to significantly curb inflammatory reactions, effectively competing with AA. The EPA/AA ratio might potentially be linked to several mechanisms in triggering inflammation, which might lead to cancer development and chronic inflammatory conditions including atherosclerosis and cardiovascular disease [20][21][22].…”
Section: Introductionmentioning
confidence: 99%